2003
DOI: 10.1044/1092-4388(2003/049)
|View full text |Cite
|
Sign up to set email alerts
|

Phonological Features of Child African American English

Abstract: The production of phonological features of African American English (AAE) was examined for 64 typically developing African American children in the 2nd through the 5th grade. Students read aloud passages written in Standard American English. Sixty of the students read the passages using AAE, and 8 different phonological features were represented in their readings. Phonological features were more frequent than morphosyntactic features. The findings as a whole support use of the taxonomy developed for this inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 30 publications
4
52
0
Order By: Relevance
“…While normative data on single word production for children of this age are available (Chirlian & Sharpley, 1982;Craig, Thompson, Washington & Potter, 2003;Haynes & Moran, 1989;Kilminster & Laird, 1978;McLeod & Arciuli, 2009;Roberts, Burchinal & Footo, 1990;Smit, Hand, Freilinger, Bernthal & Bird, 1990), to date there have been no studies which have provided population data for older children across different sample types. Moreover, studies of PSD have typically used small clinical samples rather than reference to a normative dataset.…”
Section: Introductionmentioning
confidence: 99%
“…While normative data on single word production for children of this age are available (Chirlian & Sharpley, 1982;Craig, Thompson, Washington & Potter, 2003;Haynes & Moran, 1989;Kilminster & Laird, 1978;McLeod & Arciuli, 2009;Roberts, Burchinal & Footo, 1990;Smit, Hand, Freilinger, Bernthal & Bird, 1990), to date there have been no studies which have provided population data for older children across different sample types. Moreover, studies of PSD have typically used small clinical samples rather than reference to a normative dataset.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies of language and literacy development in mismatch situation show that enhanced diglossic knowledge and awareness (referred to as "linguistic flexibility" or "linguistic awareness") correlates with increased ability to switch between the two language varieties and/or with successfully learning to read and write in the high language variety (e.g., Terry, Connor, Thomas-Tate, & Love, 2010;Terry & Scarborough, 2011;Pittas & Nunes, 2014) and that third grade typically developing African American children speakers of AAE were found to be able to switch between the two language varieties depending on the context (i.e. reading and writing versus oral communication) (Craig, Thompson, Washington & Potter, 2003;Thompson, Craig, & Washington, 2004). Consequently, it has been found that the most effective approaches toward academic success of AAE speaking children are not only those that cherish diversity and hold a high level of expectation from all students, but that first and foremost are linguistically informed in their design.…”
Section: The Development Of Diglossic Knowledge and Awareness In Oralmentioning
confidence: 99%
“…All children were tested in English, and all instruction was in English. On the basis of authentic assessment by the second author who interacted with all children individually in informal conversation, all 13 children in the experimental classroom spoke a nonmainstream dialect of English, characterized by morphological and phonological differences from the mainstream dialect that are typical of AAE (Craig et al, 2003;Washington & Craig, 2002a).…”
Section: Participantsmentioning
confidence: 99%
“…This is dialect mismatch: the fact that children from low-SES families frequently speak a nonmainstream dialect of English, whereas the language of instruction is Mainstream American English (MAE). For example, African American children from low-SES families generally use a variety of morphosyntactic, phonological, and pragmatic features that are characteristic of African American English (AAE; Craig, Thompson, Washington, & Potter;Craig & Washington, 2002;Horton-Ikard & Miller, 2004;Washington & Craig, 1998, 2002a, 2002b. These linguistic differences between MAE and AAE may make learning to read more difficult (Brown et al, 2015) and hinder academic progress more generally.…”
mentioning
confidence: 99%